2002
DOI: 10.1001/archpedi.156.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of Well-Child Care Visits in an Inner-city Clinic

Abstract: Parents of inner-city children consider WCC important. They want to hear about child health-related issues and prefer a written format. This knowledge can guide health care providers and educators during WCC visits and while teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
8
0
3
Order By: Relevance
“…26 It is disappointing to note that low-and middle-income families reported that they were less likely to receive developmental assessments, particularly because previous studies of the Medicaidaffiliated Early and Periodic Screening, Diagnosis, and Treatment program (EPSDT) program suggest that developmental screening of low-income children can result in reductions in the prevalence of problems that require later care. Studies indicated that families are more likely to utilize health services when they reflect the real and perceived needs of families.…”
Section: Discussionmentioning
confidence: 99%
“…26 It is disappointing to note that low-and middle-income families reported that they were less likely to receive developmental assessments, particularly because previous studies of the Medicaidaffiliated Early and Periodic Screening, Diagnosis, and Treatment program (EPSDT) program suggest that developmental screening of low-income children can result in reductions in the prevalence of problems that require later care. Studies indicated that families are more likely to utilize health services when they reflect the real and perceived needs of families.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7][8][9][10][11] The initial questionnaire was pilot tested on 6 practicing family physicians, revised, and then retested on 20 practicing family physicians. Postage-paid reply envelopes were consecutively numbered to allow clerical staff to track response rates.…”
Section: Methodsmentioning
confidence: 99%
“…9,11 These included response to parents' questions, physician-initiated guidance discussions, provision of age-specific multitopic guidance handouts, provision of topic-specific handouts, videotapes, and group well-child visits. A 9-point Likert scale was used, where 1 ϭ never and 9 ϭ always.…”
Section: Methodsmentioning
confidence: 99%
“…Além disso, há inúmeras questões que preocupam os pais cujo manejo não foi avaliado, mas que exigem algum tipo de intervenção do médico 20,36,37 . Portanto, o pediatra precisa estar atento às estratégias e avanços que podem melhorar seu desempenho, além da atuação multiprofissional coordenada já discutida.…”
Section: Como?unclassified
“…Há evidências de que as famílias gostariam de obter mais informações sobre a saúde da criança do que os pediatras costumam dar, que preferem receber material escrito e, mais recentemente, pela Internet 37,43,44 . Assim, é importante que o pediatra use todos os recursos audiovisuais complementares ao seu trabalho no consultório.…”
Section: Como?unclassified